Pengaruh Pengetahuan, Tingkat Risiko, Dan Motivasi Investasi Terhadap Minat Berinvestasi Di Galeri Investasi UHAMKA - Nur Azizah (Forum Dosen Indonesia, 2022)
This study aims to analyze knowledge, risk and motivation to influence interest in investing in the UHAMKA Investment Gallery with the subject of the management study program FEB UHAMKA. Hypothesis testing using multiple linear regression analysis and classical assumption testing. The sampling technique used is simple random sampling with data collection techniques carried out by giving a questionnaire using an online google application form. The data used is primary data or directly to respondents who are determined by a sample taken as many as 137 students. The results of the study that partially knowledge and investment motivation have a positive and significant effect on investment interest in investment and have a significant effect on investment interest in the UHAMKA Investment Gallery. simultaneously all variables affect the interest in investing in the UHAMKA Investment Gallery